Impact of digital health literacy on health-related quality of life in Chinese community-dwelling older adults: the mediating effect of health-promoting lifestyle - Liu, Siqi; Lu, Ya; Wang, Dan; He, Xiaochong; Ren, Wei; Kong, Dehui; Luo, Yu (Frontiers in Public Health, 2023)
Background: In the context of aging and digitalization, the development and application of digital health can help meet the growing health needs of older adults. Improving digital health literacy of older adults may be an effective way to alleviate the shortage of public health resources and improve their health-related quality of life (HRQoL). However, the impact of digital health literacy on HRQoL in older adults and the underlying mechanism remain unclear. This study intends to explore whether digital health literacy has an effect on HRQoL in community-dwelling older adults, and whether health-promoting lifestyle plays a mediating role between digital health literacy and HRQoL, while providing a theoretical basis for the scientific construction of HRQoL intervention programs for older adults. Methods: The cross-sectional study was conducted in Chongqing, China from September 2020 to April 2021. 572 community-dwelling older adults were surveyed by stratified sampling. Data on sociodemographic characteristics, digital health literacy, health-promoting lifestyle and HRQoL were collected. Univariate analysis was used to compare the differences in HRQoL among community-dwelling older adults with different sociodemographic characteristics. Pearson correlation analysis was used to explore the correlation between digital health literacy, health-promoting lifestyle and HRQoL. SPSS PROCESS macro was used to examine the mediating effect of health-promoting lifestyle between digital health literacy and HRQoL. Results: The mean score of HRQoL was 97.97 (SD 11.45). Univariate analysis showed that there were statistically significant differences in HRQoL among community-dwelling older adults with different gender, age, educational level, marital status, and monthly household income per capita (p<0.05). There were positive correlations between digital health literacy, health-promoting lifestyle and HRQoL, with correlation coefficients ranging from 0.416 to 0.706 (p<0.001). Digital health literacy was positively associated with HRQoL (β=0.210, p<0.001), and health-promoting lifestyle mediated the relationship between digital health literacy and HRQoL, with an indirect effect of 0.175 (95% Bootstrap CI 0.135-0.214). Conclusions: Digital health literacy can affect HRQoL through the mediating effect of health-promoting lifestyle. It is suggested that relevant management institutions, communities and families should strengthen the cultivation of the digital health literacy of older adults, promote their development of health-promoting lifestyle, and ultimately improve HRQoL.